Ecotheology-Based Landscape Architecture (Architecture Image Studies, 2025)
The Malalayang Beach Walk I area in Manado City has strategic potential as a public space that serves not only recreational but also educational purposes. However, its utilisation has so far been limited to tourism, necessitating a new approach that integrates ecological, theological, and pedagogical dimensions. This study aims to develop an eco- theology-based landscape architecture design that can contribute to Christian education through affective public space experiences. Using the ADDIE Research and Development model, this study seeks to address the issue of the relationship between landscape architecture and ecotheology in the Malalayang Beach Walk I area, as well as to formulate concepts and design products that implicitly support Christian education through an ecological educational approach embodied in four segments of the area. The final design product serves as an ecological-educational vehicle as well as a medium for spiritual reflection. The contribution of this research lies in the development of an interdisciplinary conceptual framework between landscape architecture and Christian ecotheology, as well as the provision of practical design products that can be used as a reference for the development of sustainable public spaces.